Signifikansi Perjanjian IUAE-CEPA Terhadap Ekspor UMKM Kota Bandung dalam Kerangka Ekonomi Islam - Minhajuddin; Abdul Rozak; Untung Novianto; Dhenahi Jerfiani Wendiyana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the potential and challenges of MSME exports KADIN Bandung City in the context of Islamic economics following the implementation of the IUAE-Comprehensive Economic Partnership Agreement (IUAE-CEPA). The increasingly dynamic development of economic globalization makes the role of MSMEs important as a driver of local and national economic growth. In the midst of these developments, the Islamic economic approach emerges as an alternative that has the potential to provide guidance in managing MSME exports in a sustainable manner. The urgency of this research lies in the importance of exports for MSMEs and the need for an in-depth understanding of the potential and challenges faced by MSMEs assisted by KADIN Bandung City in developing their exports after the implementation of the IUAE-CEPA Economic Agreement. By understanding these conditions, appropriate strategies and policies can be formulated to support the sustainable growth of MSME exports, especially in the context of Islamic economics. The purpose of this research is to identify the potentials that can be utilised and identify the challenges that need to be overcome by MSMEs assisted by KADIN Bandung City in expanding their export markets after the IUAE-CEPA economic agreement.